Randomized control study using vitamin d ( calcitriol) in preventing post total thyroidectomy transient hypocalcemia - Chung Ket, Lai (2011)
Objective: The aim of our open label randomized control study was to determine the incidence of transient hypocalcemia developing post total thyroidectomy in Kelantan (Malaysia) and the benefit of pre-operative treatment using oral vitamin D for post total thyroidectomy. Methodology: This is a randomized control study which recruits a total of 74 patients from Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II. The study was carried out over one year duration since 5th May 2009 until 30th April 2010. The ethical approval was obtained from The Research Ethical Committee (Human), Universiti Sains Malaysia and Ethical Board Clinical Research Center (CRC), Ministry of Health. Seventy four patients that underwent total thyroidectomy were randomized into two groups. Study group: 37 patients treated with oral vitamin D (calcitriol) 1.5ug/day for 2 days duration before operation followed by 1.0ug/day plus oral calcium lactate 1800mg/day for 7 days after operation. Control group: 37 patients did not receive oral Vitamin D or calcium lactate. All the patient were assessed clinically and biochemically forhypocalcemia. Result: There was no significant difference between the study and control group in terms of demographic distribution of age, sex, diagnosis, surgeon, operating duration, parathyroid gland autotransplant, and baseline level of serum calcium, phosphate and intact PTH. The incidence of post total thyroidectomy transient hypocalcemia in the study group is about 16.7% compared with control group of 75%. Among the cases, 50.0% in the study group and 64.3% in control group are symptomatic. The incidence of permanent hypoparathyroidism is 2.7%. There was significant difference in term of incidence of asymptomatic hypocalcemia and symptomatic hypocalcemia between these two groups since p value is <0.001. There was also significant difference between control and study group with regards to the trend of post-operative serum calcium changes since p value <0.001. However, there was no significant difference in the risk of developing permanent hypoparathyroidism. The post operative stay is significantly longer in control group, 4.59 days compared with study group, 3.92 days ( p value : 0.001). Conclusion: The administration of oral vitamin D pre-operatively had significantly reduced the incidence of transient hypocalcemia post total thyroidectomy.